OPTIMALISASI DIGITAL BRANDING KADIN BALI MELALUI EDUKASI CANVA DAN PENGELOLAAN MEDIA SOSIAL - Billah, Nyimas Austina Amelia Salsa; Wardani, Kadek Devi Kalfika Anggria (Jurnal Abdimas Gorontalo (JAG), 2023)
The rapid development of technology and information in recent years has made the internet a communication tool that is widely used. This phenomenon can be utilized to build digital branding today on social media. The public's enormous enthusiasm for the internet and technology can be used to attract people or audiences related to Chamber of Commerce and Industry (KADIN), especially KADIN Bali, so creative and insightful branding is needed. KADIN has a very big impact on business actors, especially MSMEs. However, not many MSMEs know what KADIN is, especially the Balinese people, so digital branding is needed. To be able to create optimal digital branding requires knowledge and understanding of KADIN Bali employees regarding creating social media content through Canva as a means of promotion and communication, as well as optimizing KADIN BALI social media by providing direct education to KADIN Bali employees regarding the stages of content creation through Canva and the utilization of Bali Chamber of Commerce and Industry social media to build company digital branding to make it more attractive, creative, and educate the public. The method used consists of three stages: introduction, implementation, and evaluation. The results of the activities had a positive impact, as KADIN Bali employees were able to increase their knowledge and abilities in creating content and using social media.